Enhanced measurement of residual chemical shift anisotropy for small molecule structure elucidation. Issue 34 (5th March 2018) - Liu, Yizhou; Cohen, Ryan D.; Gustafson, Kirk R.; Martin, Gary E.; Williamson, R. Thomas
Abstract : A simple strategy is introduced to accurately measure residual chemical shift anisotropies (RCSAs) from strong molecular alignment in the mesophase of poly-γ-(benzyl-l -glutamate). The improved data quality greatly enhances the utility of RCSA in small molecule structure analysis. Abstract : A method is introduced to measure residual chemical shift anisotropies conveniently and accurately in the mesophase of poly-γ-(benzyl-l -glutamate). The alignment amplitude is substantially enhanced over common methods which greatly benefits measurements particularly on sp 3 carbons. The approach offers significant improvements in data accuracy and utility for small molecule structure determination.